Histiocytic Disorders (Springer International Publishing, 2018)
This volume provides a comprehensive and world-class review of the field of histiocytic neoplasms and hemophagocytic lymphohistiocytosis (HLH). It reviews all the advances in the field of histiocytoses during the last ten years, particularly with regards to the genomic findings in LCH and other histiocytic neoplasms and the new suggested classification of the histiocytic disorders. Additionally, it features a state-of-the art update on the most recent treatment strategies for LCH, including the results of the last LCH-III international trial, salvage therapies such as reduced-intensity conditioning (RIC) stem cell transplant (SCT), and targeted therapies with BRAF and MEK inhibitors, as well as the challenging cases of CNS-neurodegenerative LCH and its therapeutic perspectives. For primary and secondary HLH the book updates the most recent genetic and pathophysiological findings, including macrophage-activation syndrome (MAS), and includes a special chapter on HLH in adults. Treatment chapters encompass therapy for newly diagnosed HLH and refractory disease as well as stem-cell transplantation and novel therapies. The text also highlights the most recent advances in the treatment of the uncommon histiocytic disorders, such as Erdheim-Chester disease (ECD), Juvenile xanthogranuloma (JXG) and JXG-like conditions, Rosai-Dorfman disease (RDD), and the very rare malignant histiocytoses. Written by international experts in the field, Histiocytic Disorders is a valuable resource for clinicians, researchers, fellows and residents who are interested in or manage histiocytic disorders in children and adults.